Women’s narratives on caring for people living with dementia: Exploring challenges and resources - Adaliali, Sophia (Homo Virtualis, 2025)
Dementia is a growing global health issue, affecting not only those diagnosed, but also their close environment, particularly family members, most often women, who take on caring responsibilities. The present research aims to explore the experiences of women caring for people with dementia within the Greek sociocultural context, focusing on the difficulties they encounter, the strategies they adopt to cope. The study is grounded in the phenomenological paradigm, seeking to highlight the subjective experience as it is lived and given meaning by the participants themselves. The sample consisted of 12 women caregivers of different ages and social characteristics from three major Greek cities, who care for or have cared for relatives with dementia in the past. Data were collected through semi-structured interviews that integrated appreciative inquiry activities and multimodal methods, such as photo-elicitation and projective cards, which contributed to the emergence of symbolic meanings. Interpretative Phenomenological Analysis (IPA) was used, through which common themes was identified regarding the practical and emotional challenges of caregiving, its impact on relationships and roles, fears and existential concerns, loss management and personal sources of meaning and resilience. The study concludes that caring for people with dementia is a complex and multidimensional experience, and as such requires greater recognition and support at both social and institutional levels.